Representasi Pesan Moral Dalam Film Better Days 2020 Karya Derek Tsai - Timur, Andia Jingga Langit Persada; Panuju, Redi (Jurnal Representamen, 2022)
Research on the representation of moral messages in the film Better Days 2020 by Derek Tsang examines the film's story about the story of a teenage girl who is often bullied at school and involved in a murder case with her friend. This study aims to gain an understanding of the moral messages contained in the film Better Days 2020 by Derek Tsang. The method used is qualitative, with a semiotic analysis approach of Roland Barthes. The object of this research is the film Better Days 2020, which produces the findings that: Signs in the scene in the film Better Days are semiotically displayed in realistic audio, visuals, graphics, text, and motion; The markers in each film scene are interpreted in a straightforward manner as they are; and Signs in this film are interpreted interpretively, so that the general representation of this film explores the problems of physical and mental stress in life that befell school youth from a poor environmental background, with a moral message that no matter how strong and resilient the human personality is in dealing with pressure, physically and mentally, if they are not supported by their environment, they will experience bad luck too, but as bad as fate befalls a person, it will be better for those who remain strong and endure it than those who do not have the strength and resilience.